(untitled) (Bangladesh Medical Journal, 2012)
In many developing countries including Bangladesh daily iron and folic acid supplement is given to pregnant women through health care services but with limited success. Poor compliance, inefficiency of health care services and poor quality of supplemented tablets have been implicated for such poor outcome. Several studies reported that once or twice weekly instead of daily supplementation were equally effective with reduced gastrointestinal side effects and improved patient compliance. In this study effect of once weekly administration of 120 mg of iron and 0.5 mg of folic acid was compared with same dose of daily iron and folic acid supplementation. 600 anemic pregnant women (Hb level at or below 11.9 g/ dl) at 20 weeks±15 days of pregnancy were randomly selected and allocated to one of the two treatment groups. Haematological parameters (Blood Hb, MCV and MCHC) were measured at baseline and repeated at 28th week, 36th weeks ofpregnancy and at delivery. Because of significant drop out at antenatal visits, only 57 subjects (25 in daily group and 32 in weekly group) could be followed up till delivery at the hospital. At baseline, no significant differences in haematological parameters existed between the two treatment groups except for MCV, suggesting that study participants in both groups had more or less similar haematological status at baseline. With iron and folic acid supplementation from 20th week ±15 days of pregnancy through delivery, there had been significant improvement in both Hb level and MCV in both the groups and the improvement was not significantly different between the two groups, suggesting that both weekly and daily supplementation had similar effects. Significance of this and other findings have been discussed. Further studies with larger samples have been suggested before recommending weekly supplementation for routine use. DOI: http://dx.doi.org/10.3329/bmj.v39i3.9944 BMJ 2010; 39(3)